Comparative study of stress-strain models for FRP confined concrete cylinders - Bhashya, V.; Ramesh, G.; Kumar, S. Sundar; Bharatkumar, B.H.; Krishnamoorthy, T.S.; Iyer, Nagesh R. (Journal of Structural Engineering, 2024)
Externally applied fiber reinforced polymer (FRP) composites are increasingly being used to strengthen, repair and rehabilitate civil structures. The reason behind this wide spread popularity can be attributed to its properties such as high strength to weight ratio, ease with which it can be applied at the site and the fact that there is negligible change in the dimension of the structural element. In this paper, Results of four series of the concrete cylinders wrapped with FRP are presented. First series consist of concrete cylinders wrapped with single layer carbon fiber reinforced polymer (CFRP), second series concrete cylinders wrapped with two layers CFRP, third series concrete cylinders wrapped with single layer GFRP and the fourth series consist of concrete cylinders wrapped with two layers of glass fiber reinforced polymer (GFRP). Three analytical models were taken from the literature and the experimental data were compared with the values predicted by the models. The three analytical models compared are those proposed by Toutanji, Lam and Teng, and Berthet et al. The model proposed by lam and teng was modified, predicted values of the stress-strains are compared with experimental data. Performance of predicting the stress-strain curve of this model was better comparative to other models.